Coordination, Organizations, Instiutions, and Norms in Agent System VII COIN 2011 International Workshops, COIN@AAMAS, Taipei, Taiwan, May 2011, COIN@WI-IAT, Lyon, France, August 2011, Revised Selected Papers - Cranefield, Stephen; van Riemsdijk, M. Birna; Vazquez-Salceda, Javier; Noriega, Pablo (Lecture Notes in Artificial Intelligence, 2012)
This book constitutes the thoroughly reviewed joint post-conference proceedings of two international workshops on Coordination, Organization, Institutions and Norms in Agent Systems, COIN@AAMAS 2011, held in Taipei, Taiwan in May 2011 and COIN@WI-IAT 2011, held in Lyon, France in August 2011. The 12 revised full papers presented were carefully selected for presentations. The papers are organized in topical sections on agent coordination, norm-aware agent reasoning, as well as norm creation and enforcement.